Road to redemption - Singh, Anirood (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
Lurching from day-today in the months before South Africa becomes a republic, booze-befuddled Indian private investigator Rohit Biswas does not ponder how he can secure his daughter's future after he became a widower and lost his job as police detective when he killed a man who fatally stabbed his wife. Salvation appears when a rich client hires the PI to find evidence proving his son did not rape and murder a white socialite. Fighting against seeming impossible odds in colonial-apartheid Durban and a sanctions-busting conspiracy, Biswas secures his client's acquittal. In the process he defies karma and redeems himself.
Keywords: Creative writing (Higher education) -- Research -- South Africa; Creative writing -- Fiction; South African fiction (English) -- Study and teaching (Higher); South African fiction (English) -- 21st century; Detective and mystery stories, South African (English)